Representaciones de un territorio. La frontera mapuche en los proyectos ilustrados del reino de Chile en la segunda mitad del siglo XVIII - Natalia Gándara (Historia Crítica, 2016)
The objective of this article is to analyze the representations elaborated by the authorities of the Kingdom of Chile regarding the territory of the Mapuche frontier. The research was done on the basis of four projects of territorial expansion promoted during the second half of the 18th century. The findings of this study indicate that those who planned these projects devised peaceful strategies for integrating said frontier into the Kingdom of Chile, in order to articulate said space in defensive-strategic terms and incorporate it into the colonial culture and economy. The projects were designed by intellectuals who adapted the principles of the Enlightenment to resolve the problem of the frontier, thus creating new representations regarding this space that emphasized its importance within the Spanish colonial territorial system.